2011
DOI: 10.1188/11.onf.582-586
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Coping Style on Symptom Interference Among Adult Recipients of Hematopoietic Stem Cell Transplantation

Abstract: An intervention to teach alternate coping strategies should be implemented prior to treatment and tested for prevention of symptom-related life interference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 20 publications
4
13
0
1
Order By: Relevance
“…Whilst endeavouring to maintain a positive attitude concurs with the findings of Schoulte et al (2011), who defined positivity as emotion focussed coping there is variance with the other two forms of coping styles they identified. Instrumental coping (characterised by information gathering) was found by Schoulte et al (2011) to be an adaptive coping style employed to manage a variety of physical symptoms associated with SCT.…”
Section: Copingsupporting
confidence: 77%
“…Whilst endeavouring to maintain a positive attitude concurs with the findings of Schoulte et al (2011), who defined positivity as emotion focussed coping there is variance with the other two forms of coping styles they identified. Instrumental coping (characterised by information gathering) was found by Schoulte et al (2011) to be an adaptive coping style employed to manage a variety of physical symptoms associated with SCT.…”
Section: Copingsupporting
confidence: 77%
“…Whilst this was expected for avoidance-based styles, it was not expected for those that are considered helpful in the wider literature such as planning and support-seeking (Carver et al, 1989;Taylor & Stanton, 2007). Studies examining the post-acute period of HSCT have not observed reliable effects of these latter styles (Schoulte et al, 2011;Wells et al, 2009) but it is possible that the circumstances of acute HSCT may render many coping strategies ineffective or counterproductive. For example, an adverse effect of planning has been noted in acute cancer care but not subsequent periods (Carver et al, 1993).…”
Section: Perceptions Of Hsct and Copingmentioning
confidence: 98%
“…Each style comprises two items rated on a 4-point Likert scale with total scores from 0-6 as a continuous variable (higher scores denoting more frequent use) (Carver, 1997). The instrument has good construct, concurrent, and predictive validity in relation to emotional well-being and adjustment in different clinical populations including HSCT (Bautista & Erwin, 2013;Cooper, Katona, Orrell, & Livingston, 2008;Folkman & Moskowitz, 2004;Hooper, Baker, & McNutt, 2013;Knowles, Cook, & Tribbick, 2013;Meyer, 2001;Schoulte et al, 2011). Some limitations to reliability have been reported with Cronbach's α between 0.50-0.90 and test-retest reliability coefficients between 0.42-0.89 (6-8 weeks) (Carver, 1997;Carver et al, 1989).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations